Improving the virtual communication efficiency as a fundamental factor of successful marketing strategy - Syerov, Yu.; Fedushko, S.; Trach, O. (Academic Publishing House of the Agricultural University Plovdiv, 2016)
This article decided an important scientific task of developing methods for increasing the virtual communities’ efficiency as a key factor of their marketing strategy. Different types of virtual communities were analyzed, and their place in WWW was defined. The analysis of virtual communities’ efficiency criteria was carried out and complex of numerical indexes of effectiveness of the virtual communities was defined. Analyzing and defining characteristics and classification of virtual community members were presented. The method of improving the effectiveness of the community functionality was described.
Keywords: marketing strategy; World Wide Web; virtual community; virtual community member